Where the United States spends its spine dollars: expenditures on different ambulatory services for the management of back and neck conditions. - Davis, Matthew A.; Onega, Tracy; Weeks, Bill; Lurie, Jon D. (Spine, 2012)
Study Design Serial, cross-sectional, nationally representative surveys of non-institutionalized adults.